Risk Factors for Classical Hysterotomy in Twin Pregnancies - Osmundson, Sarah S. (Obstet Gynecol, 2015)
OBJECTIVE: To describe the rate of classical hysterotomy in twin pregnancies across gestational age and examine risk factors that increase its occurrence. METHODS: This is a secondary analysis of the Cesarean Registry, a cohort study of women who underwent a cesarean delivery or a trial of labor after cesarean delivery at 19 academic centers between 1999 and 2002. Our study included all women with twin pregnancies and a recorded hysterotomy type who underwent cesarean delivery between 23 0/7 and 41 6/7 weeks of gestation. Primary exposures were gestational age at delivery and combined birth weight of twin A and twin B. Multivariate logistic regression was used to study factors thought to influence hysterotomy type including maternal age, body mass index (BMI) at delivery, obesity (BMI 30 or higher), nulliparity, labor, prior cesarean delivery, emergent delivery, and fetal presentation at delivery. RESULTS: Of 1,820 women meeting inclusion criteria, 125 (7%) underwent a classical hysterotomy. The risk of classical hysterotomy was greatest at 25 weeks of gestation (41%) and declined thereafter. The adjusted odds ratio (OR) for cesarean delivery declined as gestation age advanced (OR 0.87, 95% confidence interval 0.78–0.98). African American race and emergent delivery were associated risk factors for classical hysterotomy at 32 weeks of gestation or greater. CONCLUSION: Among women with twin pregnancies who deliver by cesarean, the incidence of classical hysterotomy is inversely related to gestational age but does not exceed 50% at any week; African American race and emergent delivery are associated risk factors at 32 weeks of gestation or greater. LEVEL OF EVIDENCE: II